Macroeconomic Developments and Prospects in Low-Income Developing Countries. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2018)
This paper is the fourth in a series that examines macroeconomic developments and prospects in Low Income Developing Countries (LIDCs). LIDCs are Fund member countries where gross national income (GNI) per capita lies below a threshold level and where external financial linkages and socioeconomic indicators have not lifted them into emerging market status. There are 59 countries in the LIDC grouping, accounting for about one-fifth of the world's population and 4 percent of global output. The paper examines macroeconomic trends across LIDCs in recent years, contrasting key features of the current situation with the period prior to the 2014 decline in commodity prices. Particular attention is given to the evolution of fiscal positions and public debt levels, including detailed analysis of the drivers of debt accumulation and the current severity of debt vulnerabilities. The analysis is grounded in, and draws on, the analysis and databases used to compile the World Economic Outlook: this report drills down into the WEO database to look in detail at the experience of LIDCs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet